Introduction to the work of Cynthia Enloe - UNSW eLearning (2018)
VideoScribe animation that introduces the work of Cynthia Enloe and in particular her book "Bananas, Beaches and Bases: Making Feminist Sense of International Politics" in relationship to power, politics and International Relations. Scripted and read by Professor Laura Shepherd.
Keywords: approches et analyses; cours; discipline; histoire et politique; pol5480; premier cycle; rapports de pouvoir; ressource en ligne; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

Whose Land Is It Anyway?: a Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Federation of Post-Secondary Educators of BC, 2018)
We are pleased to announce the publication of Whose Land Is It Anyway? A Manual for Decolonization; inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The book contains two essays from Manuel, described as the Nelson Mandela of Canada, and essays from renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. FPSE is honoured to support this publication.
Disponible gratuitement en ligne à l'adresse suivante: https://fpse.ca/decolonization_manual_whose_land_is_it_anyway Le texte de Jacobs, Beverly (2013). Decolonizing the Violence Against Indigenous Women, a été donné en lecture au cours POL4105
Keywords: amériques; approches et analyses; canada; cours; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Contre misogynoir. Des Caribéennes francophones entre black feminism et afroféminisme - Melyon-Reinette, Stéphanie (https://www.archipelies.org:443, 2018)
Misogynoir : un terme qui résume parfaitement la réalité sociale et identitaire des femmes noires aux États-Unis, comme en France hexagonale : il désigne tous les manifestations et comportements discriminatoires à l’égard des femmes noires et de couleur basés tout à la fois sur le sexisme, le racisme ou le colorisme. Si cette terminologie est récente, le phénomène est aussi ancien que le monde binaire (blanc vs noir) dont il procède : le système plantationnaire et ses avatars. Par ailleurs, on ne peut négliger les aspects intersectionnels de la période-même avec les classes phénotypico-sociales. Dans cet article, nous interrogerons la place et le positionnement des Caribéennes francophones dans le cadre des mouvements féministes de Paris. Ainsi, prendrons-nous en compte la pluriethnicité des communautés féminines noires de France et les liens qu’elles tissent avec ces différentes aires d’implantation : Région parisienne, Caraïbe et Amérique noire.
ISSN: 2777-5909 Publisher: CRILLASH (Centre de recherches interdisciplinaires en lettres, langues, arts et sciences humaines)/Presses de l’Université des Antilles
Keywords: afro-féminisme; approches et analyses; cours; fem3300; féminisme afroaméricain; féminisme décolonial; histoire et politique; premier cycle; racisme; ressource en ligne; sexisme; système colonial; systèmes d'oppressions; thématiques; violences